Structure and Dynamics of Elementary Matter 2004
DOI: 10.1007/978-1-4020-2705-5_48
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Large Extra Dimensions

Abstract: String theory suggests modifications of our spacetime such as extra dimensions and the existence of a mininal length scale. In models with addidional dimensions, the Planck scale can be lowered to values accessible by future colliders. Effective theories which extend beyond the standart-model by including extra dimensions and a minimal length allow computation of observables and can be used to make testable predictions. Expected effects that arise within these models are the production of gravitons and black h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A suppression of the backward peak is observed for the BH events and is seen to depend on the kinematical region used. Another possible signature is the direct detection of BH relics which are BHs left over at the end of the Hawking decay of mass near the higher-dimensional Planck Mass (∼ 1 TeV) which may be stable 16,17,18 . A preliminary study of the ability of ALICE to detect charged BH relics of 2 TeV mass is shown in Figure 8.…”
Section: Quantitative Calculations Of Mini-bh Production At the Lhc A...mentioning
confidence: 99%
“…A suppression of the backward peak is observed for the BH events and is seen to depend on the kinematical region used. Another possible signature is the direct detection of BH relics which are BHs left over at the end of the Hawking decay of mass near the higher-dimensional Planck Mass (∼ 1 TeV) which may be stable 16,17,18 . A preliminary study of the ability of ALICE to detect charged BH relics of 2 TeV mass is shown in Figure 8.…”
Section: Quantitative Calculations Of Mini-bh Production At the Lhc A...mentioning
confidence: 99%
“…A promising realization of these ideas is represented by "TeV-Scale Gravity" where it is possible to introduce a unification scale, M * , as low as some TeV ( [1], [2]). If these theoretical models are correct new exciting phenomenology ( [3], [4]) is going to be observed at future colliders, as the physics of unified interactions, including quantum gravity, will become accessible. No doubts, the most spectacular expected event is a mini black hole production and decay [5].…”
Section: Introductionmentioning
confidence: 99%